Perceptions of Teachers and Pupils of Causes of conflict in Primary schools in Zimbabwe: A case study of Gweru District Primary Schools. - Saiden, Thondhlana; D., Makawa J. (Advances in Social Sciences Research Journal, 2017)
Conflicts in organisations are inevitable. For conflict to be managed and transformed appropriately one needs to be aware of the causes of these conflicts. This study was necessitated by a realisation that heads of schools used short-fix interventions to conflicts. Teachers also used short- fix interventions to conflicts. The state of affairs affected negatively teaching, learning and peace in the primary schools. The study focused on the causes of conflict in the primary schools in a bid that appropriate interventions could therefore be established. The sample of the study consisted of 134 teachers, 120 children and one District School’s inspector for the district under study. The sample was purposively chosen. A qualitative research methodology was employed. A case study design was adopted. The major findings of the study were; shortage of resources, dictatorship, competition, gossip related to teachers and name calling, bullying, stealing, unfair treatment, abuse, hatred and rudeness related to pupils. The causes of conflict did not differ between urban and rural areas. Some of the recommendations were; that schools in clusters were to pool resources, schools were to practise multicultural education and inter- faithism and schools were to establish a cooperative context.